Truths and Lies from the Polysomnography ECG Recording: An Electrophysiologist Perspective - Adrian Baranchuk; Christina Quinlan; Kevin Michael; Christopher S. Simpson; Damian P. Redfearn; Michael Fitzpatrick (Case Reports in Medicine)
Polysomnography remains the gold standard for diagnosis of Sleep Apnea (SA) and evaluation of the apnea/hypopnea index (AHI) which is used as the primary index of SA severity. The electrocardiogram (typically a single lead) obtained during the polysomnographic study is usually used to report the association between SA and cardiac rhythm disturbances. These findings help in guiding medical decisions but they could also represent a source for confusion. Electrophysiologists are frequently consulted to determine whether interventions need to be taken. We present 2 cases where the ECG during a polysomnography study required the intervention of an electrophysiologist to help with management.